Fostering a Positive Learning Climate through Classroom Management: A Case Study from Rural Indonesian Elementary Education - Suci Anggraini; Azizatul Khairi; Manap Somantri (Yayasan Sembilan Pemuda Indonesia, 2026)
This qualitative case study explored the implementation of positive learning climate-based classroom management at SD Negeri 4 Muara Rupit, a public elementary school in rural Indonesia. Participants included three classroom teachers, the school principal, two vice principals, and twelve students, selected purposively. Data were collected over three months through classroom observations, semi-structured interviews, and documentation analysis involving lesson plans, classroom rules, teaching modules, reflective notes, and photographs. Data analysis was conducted iteratively through coding, categorization, thematic display, and verification across data sources. Findings revealed that classroom management was implemented through four interconnected processes: systematic planning, interactive implementation, continuous evaluation, and adaptive strategies for addressing classroom challenges. Planning involved participatory classroom rules, flexible seating arrangements, supportive physical environments, and active learning strategies. Implementation was characterized by communicative teacher-student interaction, positive reinforcement, educative discipline, emotional support, and collaborative learning. Evaluation occurred continuously through teacher reflection and observation of student participation, interaction quality, and classroom atmosphere. Supporting factors included school leadership support, teacher collaboration, and cooperative student behavior, whereas inhibiting factors comprised diverse student characteristics and limited educational facilities. Despite these challenges, teachers demonstrated reflective and flexible practices that supported students’ academic and socio-emotional development. The study concludes that positive learning climate-based classroom management contributes to safe, participatory, and supportive elementary classrooms. Limitations include the single-site design and limited student voice. The findings imply a need for professional development in reflective practice, positive discipline, and adaptive classroom management.